Household Solid Waste Management, Attitude and Practices: A Case Study of Residents in the University of Nigeria Nsukka Staff Quarters. - Ononuju, Amaka Harry; Romanus, Chidinma W.; Dibia, Samuel Ifeanyi Chris; Iwuagwu, Tochi Emmanuel; Usman, Kato G. (Journal of Home Economics Research, 2024)
The study investigated attitudes and practices of households towards solid waste management within the University of Nigeria, Nsukka staff quarters. Specifically, the study determined: attitude of the households towards solid waste management and their solid waste management practices. The study adopted survey research design. Population for the study consisted of 599 households in 517 senior staffs and 82 junior staff quarters. Questionnaire was used for data collection. Mean, standard deviation, frequency, percentages, ANOVA and Chi-Square were used for data analysis. Results show five negative attitude indicators, including, among others, “ being willing to pay a fee or contribute towards improved waste management services within the staff quarters (x =2.44), feeling satisfied with the current solid waste practice of open dumping within the University of Nigeria Nsukka staff quarters (x =1.73). Households had moderate practice on three indicators including waste segregation (54.5%), open disposal of waste (42.4%), and high practice on three items, namely storing waste in plastic bag before disposal (75%). There was a significant difference in households’ attitude towards solid waste management based on household size (F-value= 7.077, p-value= .000). There was no significant difference in household solid waste management practices based on household size (X2 = .970, P-value = .809). The study concludes that households in UNNSQs have more negative attitude indicators and moderate practice towards solid waste management. The study recommends provision of conveniently accessible public bins within the staff quarters by the school management will improve solid waste management practices. Households should be involved in the planning and implementation of solid waste management initiatives to help households develop more positive attitude towards solid waste management.